Bioecologia e controle microbiano de sarsina violascens (Herrich-schaeffer, 1856) (Lepidoptera: Lymantriidae) em Eucalyptus spp - Winckler, Daniela Cristina Firmino [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
A espécie Sarsina violascens (Herrich–Schaeffer, 1856) (Lepidoptera: Lymantriidae) é relatada como praga primária em plantios de eucalipto e teve sua primeira ocorrência registrada em 1975. No período de 2006 a 2009 houve grandes surtos dessa praga, causando desfolhamento intenso em plantios de eucalipto no norte da Bahia. Apesar dos estudos feitos no passado terem considerado espécies de eucalipto, há pouca informação sobre a suscetibilidade de clones híbridos de eucalipto à mariposa violácea. O presente trabalho teve por objetivo avaliar a biologia de S. violascens em diferentes espécies e híbridos de eucalipto e em diferentes temperaturas, além de avaliar a eficiência de entomopatógenos no controle de S. violascens. No experimento 1 a biologia de S. violascens foi determinada nas espécies Eucalyptus grandis, E. urophylla e dois híbridos de E. grandis x E. urophylla (‘urograndis’). Os parâmetros avaliados foram duração e viabilidade dos estágios larval, pupal, adulto e de ovo e do ciclo total. No experimento 2 foi selecionada a espécie E. urophylla como padrão e avaliou-se o efeito de diferentes temperaturas (18, 22, 26 e 30oC) no desenvolvimento de S. violascens, avaliando-se os mesmos parâmetros anteriores. Os resultados obtidos no experimento 1 revelaram que E. urophylla ofereceu melhores condições para odesenvolvimento de S. violascens, com maior viabilidade larval (85,3 %), pupal (78,7 %) e de ovos (72,6 %), e menor duração do ciclo total (54,4 dias). A espécie E. grandis foi considerada a menos adequada ao desenvolvimento de S. violascens, revelando baixas viabilidades larval (29,2 %) e pupal (28,9 %). Os resultados obtidos com os dois híbridos foram intermediários comparativamente com as espécies testadas. No experimento 2 as temperaturas de 18, 22 e 26°C foram adequadas para o desenvolvimento e reprodução de S. violascens, com alta viabilidade...

Defoliator lepidopterous are one of the main Eucalyptus pest groups in Brazil. There are records of caterpillars outbreaks since 1940, with important occurrences during 1980’s to 1990’s. The species Sarsina violascens (Herrich–Schaeffer, 1856) (Lepidoptera: Lymantriidae), named as violet moth, is related as pest in eucalypts plantations since 1975 and during 2006 to 2009, this species has occurred in outbreaks, causing intense defoliation in eucalypt plantations in Northern Bahia, Brazil. Despite studies in the past have considered species of eucalyptus, there is little information about susceptibility of Eucalyptus hybrid clones to violet moth. This study aimed to determine the biology of S. violascens in different species and hybrids of eucalyptus and in different temperatures. The insects were observed diary to evaluate life cycle in different species of eucalyptus (experiment 1) and in different temperatures (experiment 2). In experiment 1 were tested the following species: Eucalyptus grandis, E. urophylla and two hybrids of E. grandis x E. urophylla (‘urograndis’). The parameters evaluated were: duration and viability of larvae, pupae, adult and eggs phases and total life cycle. In experiment 2 was chose the species E. urophylla as standard and evaluated the effect of temperatures of 18, 22, 26 and 30oC, considering the same previous parameters. The results obtained in experiment 1 showed that E. urophylla offered better conditions to S. violascens development and reproduction, due the higher larvae, pupae and eggs viability, and shorter total life cycle duration. The species E. grandis was considered as less adequate to S. violascens development and reproduction, with low larvae and pupae viability. To the two hybrid clones, the results were intermediary comparatively with tested species. In experiment 2 temperature of 18°C showed the most adequate to S. violascens... (Complete abstract click electronic access below)
Keywords: Eucalipto; Lagarta desfolhadora; Biologia; Mariposa; Caterpillar; Eucalypt; Violet Moth; Lepidoptera; Biology; Bioinsectides